Deep Vein Thrombosis (DVT) and Abdominoplasty: A Holistic 8-Point Protocol-Based Approach to Prevent DVT. (15th January 2021) - Sforza, Marcos; Husein, Rodwan; Saghir, Reyan; Saghir, Noman; Okhiria, Renee; Okhiria, Terrell; Sidhu, Manu; Zaccheddu, Renato
Abstract: Background: Plastic surgery as a specialty is afflicted with one of the highest incidence rates of thromboembolic events, with abdominoplasty procedures known to assimilate the greatest rates of deep vein thrombosis (DVT). Objectives: The aim of this study was to develop a prophylactic protocol to reduce the rate of DVT occurrence postabdominoplasty. Methods: Over a 7-year period 1078 abdominoplasty patients were enrolled onto a holistic 8-point prophylaxis protocol. For a 4-week period before the operation all patients were required to stop smoking, and to cease hormone replacement therapy and combined oral contraception. All patients were required to have a preoperative BMI of less than 40 kg/m 2 . Participants were supplied with compression stockings, external pumping devices, and enoxaparin. Individuals with a history of DVT were also required to be 1-year treatment free prior to surgery. Furthermore, the protocol required postoperative ambulation of fit patients within 4 hours. Results: Between 2008 and 2013, no incidence of DVT was recorded in all 1078 abdominoplasty surgery patients, indicating the potential for this protocol to lead to a significantly lower incidence than any previously published methodology. Previous studies of DVT incidence were reviewd to identify rates statistically significantly similar to our sample, thereby providing conservative incidence rate estimates. Conclusions: This 8-point DVT prophylaxis protocol is the first noncriteria-based inclusive protocol aimed at preventing abdominoplasty-associated DVT. A holistic and procedure-specific approach to prophylaxis can drastically reduce the occurrence of DVT in abdominoplasty surgery. With over 116, 000 procedures performed annually in the United States, abdominoplasty has become one of the most popular and sought-after surgeries in the plastic and cosmetic field. 1 Despite its ever-increasing popularity and the advancement of techniques, abdominoplasty—as with any other surgery—has its complications, including infection, seroma, hematoma, thrombosis, embolism, scarring, and even death. Complication rates as high as 37% have been reported, with some studies reporting a 16% major complication rate. 2 One of the most serious and troubling complications for both surgeon and patient is deep vein thrombosis (DVT). With over 1 million patients tested, an estimated 250, 000 cases of DVT are diagnosed per year in the United States alone. Level of Evidence: 4: